High-risk features of basilar artery atherosclerotic plaque - Li, Shaojun; Wei, Jiana; Huang, Ruiyun; Li, Chenghao; Chen, Hongbing; Qiu, Zhihua; Jiang, Yongjun; Wu, Li (Frontiers in Neurology, 2022)
Introduction High-resolution magnetic resonance imaging (HR-MRI) is used to characterize atherosclerotic plaque. The present study aimed to determine the high-risk features of the basilar artery (BA) atherosclerotic plaque. Methods Patients with advanced BA stenosis were screened. The features including the ruptured fibrous cap (RFC), lipid core, intraplaque hemorrhage (IPH), plaque enhancement, and calcification were assessed by using high-resolution MRI. The relationship between the features and acute infarction was analyzed. Results From 1 June 2014 to 31 December 2018, a total of 143 patients with 76 new strokes were included. RFC was identified in 25% of symptomatic and 10.4% of asymptomatic patients. IPH was identified in 48.7% of symptomatic and 25.4% of asymptomatic patients. RFC (3.157, 95% CI 1.062 to 9.382, p = 0.039) and IPH (2.78, 95% CI 1.127 to 6.505, p = 0.026) were independent risk factors for acute infarction. Conclusion Our study showed that RFC and IPH of BA plaque were independent risk factors for acute infarction.